Effective Strategies for Retaining and Nurturing employees in Organizations - Suriati, Suriati; Ibrahim, Muhdi B. Hi; Irawan, Andri; Akbar, Muhammad Aldrin; Yendra, Yendra (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
The study aims to investigate effective strategies for enhancing employee retention and fostering a nurturing work environment in organizations. Employing a comprehensive literature review approach, this research synthesizes key findings regarding financial incentives, career development opportunities, supportive work environments, and effective leadership practices in promoting employee retention. Methodologically, the study utilizes a qualitative analysis of existing literature to identify trends, patterns, and insights related to the retention strategies employed by organizations. The findings suggest that competitive salaries, performance bonuses, comprehensive benefits packages, and career advancement pathways are instrumental in attracting and retaining top talent. Additionally, fostering a supportive work environment characterized by open communication, transparent leadership, inclusivity, and empowerment significantly contributes to employee satisfaction and retention. Effective leadership practices, such as transformational leadership and visionary communication, play a critical role in inspiring employee engagement and commitment. Implications of the study underscore the importance of organizations adopting a multifaceted approach to retention, integrating financial incentives, career development opportunities, supportive work environments, and effective leadership practices. By recognizing and addressing the diverse needs and preferences of employees, organizations can create a positive workplace culture conducive to long-term employee retention and organizational success.